The effectiveness of early foreign language learning in the Netherlands - de Bot, Kees (Studies in Second Language Learning and Teaching, 2014)
This article reports on a number of projects on early English teaching in the Netherlands. The focus of these projects has been on the impact of English on the development of the mother tongue and the development of skills in the foreign language. Overall the results show that there is no negative effect on the mother tongue and that the gains in English proficiency are substantial. Given the specific situation in the Netherlands where English is very present, in particular in the media, a real comparison of the findings with those from other countries is problematic.